Economic Losses of Non-Exclusive Breastfeeding in East Nusa Tenggara - Estro Dariatno Sihaloho; Rahma Rahma; Wandira Larasati Senja; Pipit Pitriyan; Adiatma Y.M Siregar (UNIVERSITAS INDRAPRASTA PGRI, 2019)
The knowledge of the importance of exclusive breastfeeding is still low in East Nusa Tenggara. Many families have started providing complementary foods like bananas or porridge, to their babies when they are only 2 months old. Providing complementary foods since babies 2 months old will increase the possibility of diarrhea and pneumonia/respiratory of babies. This study has three objectives. The first objective tries to estimate the economic impact of non-breastfeeding in East Nusa Tenggara. The second objective tries to calculate the health system medical cost and the third objective tries to calculate the patient/non-medical cost. This paper calculates the patient cost from 153 patient data collected from Kupang district in 2016. This paper estimates the economic impact by combining the health system cost, patient/non-medical cost with the prevalence data from IDHS 2012. This study finds that total economic losses caused by non-exclusive breastfeeding due to diarrhea and pneumonia/respiratory about US 2,718,497. This study finds the average cost due to non-exclusive breastfeeding for diarrhea cases about US 9.3 and PRD cases about US8.4.